How many fingers am I holding up? The answer depends on children's language background. Issue 4 (2nd January 2019) - Nicoladis, Elena; Marentette, Paula; Pika, Simone
Abstract: Monolingual English‐speaking preschool children tend to process number gestures as unanalyzed wholes rather than use the one‐to‐one (finger‐to‐quantity) correspondence. By school age, however, children can use the one‐to‐one correspondence. The purpose of the present studies was to test whether children learn one‐to‐one correspondence through exposure to a variety of finger configurations to convey a single quantity. In Study 1, we compared children with exposure to multiple one‐to‐one configurations, that is, French‐English and German‐English bilingual children, to English monolingual children who see consistent representations. As predicted, the bilingual children performed better in interpreting unconventional number gestures. In Study 2, we compared Chinese‐English bilingual children who knew arbitrary one‐handed Chinese numbers gestures for quantities 6–10 to Chinese‐English bilingual children who did not know these gestures, as well as to monolingual English speakers. Chinese‐English bilinguals who knew the arbitrary gestures were more likely to interpret unconventional gestures arbitrarily (i.e., influenced by the written and/or Chinese gesture forms). These children did not differ from English monolinguals in the interpretation of unconventional gestures. These results are consistent with the argument that children can become sensitive to the one‐to‐one correspondence in number gestures with exposure to multiple configurations for the same quantity. Abstract : Bilingual children showed some advantages in interpreting unconventional gestures over monolingual children. These results suggest that greater exposure to different types of number gestures leads children to greater sensitivity to the one‐to‐one correspondence available in number gestures.